Whole genome sequencing reveals translocation breakpoints disrupting TP63 gene underlying split hand/foot malformation in a Chinese family. Issue 3 (20th January 2021) - Peng, Ying; Yang, Shuting; Xi, Hui; Hu, Jiancheng; Jia, Zhengjun; Pang, Jialun; Liu, Jing; Yu, Wenxian; Tang, Chengyuan; Wang, Hua
Abstract: Background: Split hand/foot malformation (SHFM) is a congenital limb developmental disorder, which impairs the fine activities of hand/foot in the affected individuals seriously. SHFM is commonly inherited as an autosomal dominant disease with incomplete penetrance. Chromosomal aberrations such as copy number variations and translocations have been linked to SHFM. This study aimed to identify the genetic cause for three patients with bilateral hand and foot malformation in a Chinese family. Methods: Karyotyping, single‐nucleotide polymorphism (SNP) array, whole exome sequencing, whole genome sequencing, and Sanger sequencing were applied to identify the pathogenic variant. Results: Karyotyping revealed that the three patients had balanced reciprocal translocation, 46, XX, t(3;15) (q29;q22). SNP array identified no pathogenic copy number variation in the proband. Trio‐WES (fetus–mother–father) sequencing results revealed no pathogenic variants in the genes related to SHFM. Whole‐genome low‐coverage mate‐pair sequencing (WGL‐MPS), breakpoint PCR, and Sanger sequencing identified the breakpoints disrupting TP63 in the patients, but not in healthy family members. Conclusion: This study firstly reports that a translocation breakpoint disrupting TP 63 contributes to the SHFM in a Chinese family, which expands our knowledge of genetic risk and counseling underlying SHFM. It provides a basis for genetic counseling and prenatal diagnosis (preimplantation genetic diagnosis) for this family. Abstract : We firstly report three patients in a Chinese family with genetics diagnosis of TP63 translocation related with SHFM4. This identification expands our knowledge of genetic risk and counseling underlying SHFM.